Doenças de bovinos no Sul do Brasil: 6.706 casos - Lucena, Ricardo Barbosa de (2009)
The diseases affecting cattle in Southern Brazil were studied through a review of the necropsy reports filed at the Laboratório de Patologia Veterinária of the Universidade Federal de Santa (LPV-UFSM), Rio Grande do Sul and pertaining to the examination of 6.076 cattle during 1964-2008. Of those exams 29.9% were necropsies performed at the LPV-UFSM and 79.1% were mailed-in organ fragments from necropsies performed at the field by veterinary practitioners. Autolysis and non-representative sampling o mailed in organs were the main reasons for non-conclusive diagnosis. Poisoning by Senecio spp. was the main cause of death in cattle in this study and poisonous plants together with toxi-infections accounted for 22.8% of the cases with conclusive diagnosis. Inflammatory diseases together with parasitic diseases accounted for more than 30% of cattle diseases and babesiosis and anaplasmosis were the main diseases in this category. Other categories were distributed in the following order: neoplasms and tumor-like lesions (13.88%), diseases caused by physical agents (2.7%), metabolic and nutritional diseases (2.46%), circulatory disturbances (1.4%), degenerative diseases (1.1%), developmental disorders (0.54%), iatrogenic diseases and sundry lesions. The high prevalence of tumors in cattle in this study was attributed to the chronic ingestion of Pteridium aquilinum, a common toxicosis in the region. The main diseases in cattle from the studied region are related to environmental factors associated to the predominantly husbandry practices adopted in the region.